Key Determinants of Fintech Peer-to-Peer Lending Usage Intentions: Insights from Bandung City - Putra, Okta Eka; Pramayuda, Agung; Rohaeni, Tanti; Tarigan, Vera Yessica; Ariffin, Ariezan Zainal (PT Agung Media Publisher, 2025)
This study aims to identify and analyze the key factors influencing the intention to use fintech peer-to-peer (P2P) lending services in Bandung City, addressing a significant area of financial technology adoption in emerging markets. This research uses a quantitative accidental sampling method, namely a non-probability sampling technique to survey 428 residents of Bandung City who use P2P lending services. Data were collected through questionnaires and analyzed using multiple linear regression to evaluate the impact of various independent variables on usage intention. The analysis revealed that Personalization, Accessibility, and Enhanced Effectiveness have a positive and statistically significant influence on the intention to use P2P lending. Conversely, Loan Approval Speed demonstrated a negative and statistically significant effect. Social Factors, however, were found to have no significant impact on usage intention. These findings contribute to the literature on fintech adoption, highlighting the importance of service personalization and accessibility while identifying areas for improvement, such as streamlining loan approval processes. The insights provided can inform strategies for both service providers and policymakers in fostering responsible P2P lending adoption in Bandung City. This research underscores critical determinants of P2P lending usage intentions and provides actionable insights for enhancing the effectiveness and appeal of financial technology services in Bandung City.